Phytochemical Profiling of Different Cassia Species A: Review - Kabila, Bhavna (International Journal of Pharmaceutical & Biological Archive, 2017)
The plants have been used in traditional medicines over a long period throughout the world. Species of genus Cassia contain many important phytochemicals and are well known in folk medicines. These phytochemicals exhibit interesting biological and pharmacological properties. Alkaloids, flavonoids, tannins, saponins etc are some of the useful phytoconstituents used for the preparation of various medicines. This review is compiled to document the alkaloids, flavonoids, saponins and tannins present in species of the genus Cassia using different solvents. It will throw a light on the treasure of phytochemicals with a potential for pharmaceutics. Based on this information, species can be selected and characterized to meet the requirements of human health care system.